2021
DOI: 10.31234/osf.io/4hyn3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic cognitive flexibility

Abstract: Cognitive flexibility, or the ability to flexibly switch between different task sets, is often operationalized using performance on voluntary task switching (VTS) paradigms. In VTS paradigms, performance is commonly measured by examining reaction time, accuracy, the effects of switching tasks on reaction time and accuracy, and the rate at which participants choose to switch tasks. Previous literature has frequently examined these measures in terms of overall task averages. Instead, the current work examines wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…However, there was no support for the hypothesis that the uncertain nature of probabilistic reward slowed learning the cue-reward associations, F (3, 156) = .660, p = .578, η 2 G = .003. We have previously demonstrated that this reduction in switching occurs across different VTS paradigms and possibly reflects early fatigue Imburgio and Orr, 2021. This is also consistent with previous EEG work showing that fatigue effects are most pronounced when working memory is involved (Petruo et al, 2018).…”
Section: Voluntary Switch Ratesupporting
confidence: 91%
“…However, there was no support for the hypothesis that the uncertain nature of probabilistic reward slowed learning the cue-reward associations, F (3, 156) = .660, p = .578, η 2 G = .003. We have previously demonstrated that this reduction in switching occurs across different VTS paradigms and possibly reflects early fatigue Imburgio and Orr, 2021. This is also consistent with previous EEG work showing that fatigue effects are most pronounced when working memory is involved (Petruo et al, 2018).…”
Section: Voluntary Switch Ratesupporting
confidence: 91%